Geochemistry of Formation Water and Its Implications for Petroleum Source Rocks in the Fengcheng Formation, Mahu Depression, Xinjiang, China - Wang, Jian; Zhou, Lu; Liu, Jin; Zhang, Xinji; Luo, Xiaojing; Zhu, Rong; Wu, Yong; Ren, Zhaoyan; Dick, Jeffrey (Frontiers in Earth Science, 2022)
Geochemical properties of formation water reflect the sedimentary environments and the sealing conditions of the formation, which are of great significance for oil and gas exploration. In this research, the formation waters in the deep Permian Fengcheng Formation in the Mahu Depression were studied by analysis of chemical composition, stable isotopes, and the homogenization temperatures and salinities of fluid inclusions. The results show that the formation water is NaHCO3-type with high salinity, high HCO3-, low concentrations of Ca2+ and Mg2+ and high pH. The overall sealing of the formation is well maintained. Na2SO4-type water was found in some places with poor preservation of oil and gas. The fluid geochemistry and alkaline mineral distribution in the strata, which are dominated by deep fine-grain mixed deposits, indicate that the main body of the Fengcheng Formation was deposited in an alkaline lake sedimentary environment. The isotopic signatures are characterized by high δ13C, negative δ18O, and light strontium and heavy boron isotopes in the strata near the deep fault zone, which indicate that the Fengcheng formation may have been affected by deep hydrothermal fluids. From the first member to the third member of the formation, the salinity first increases and then decreases. This low-high-low trend corresponds to the initial stage of alkaline lake development followed by strong alkali formation and a final stage of water retreat. The coincidence between the spatial distribution of alkaline minerals, high-salinity formation water and source rocks indicates that the alkaline lake environment can form high-quality source rocks with good petroleum generation capacity.